Response Asymmetry in Spillover Volatility: An Empirical Study in the Indonesia and Singapore Stock Market - Saadah, Siti (UI Scholars Hub, 2013)
Following the blueprint of the ASEAN integration 2015, the integration of the financial markets in this region will increase. This study investigates the existence of a volatility spillover from the Singaporean stock market into Indonesia, including its transmission pattern. Singapore, as an advanced country in the ASEAN region, has played an important role as the information leader in the market of this region, so that it is very possible that the shocks in the Singapore’s stock market will be transmitted to another stock market in this region. Using TGARCH (1,1) model specification regarding the data of the daily return of the Indonesia market index (IHSG) for the period of January 2008 – August 2012, it is observed that the shock that took place in the Singapore stock market is immediately transmitted to the Indonesia stock market with two important asymmetric patterns. The transmission of the shock from the Singapore stock exchange becomes stronger when this market (1) experiences a negative return, and (2) is in the bearish phase.